Measuring the subgingival microbiota in periodontitis patients: Comparison of the surface layer and the underlying layers. (20th December 2019) - Liu, Guojing; Chen, Feng; Cai, Yu; Chen, Zhibin; Luan, Qingxian; Yu, Xiaoqian
Abstract: Periodontitis is a major cause of tooth loss in adults that initially results from dental plaque. Subgingival plaque pathogenesis is affected by both community composition and plaque structures, although limited data are available concerning the latter. To bridge this knowledge gap, subgingival plaques were obtained using filter paper (the fourth layer) and curette (the first‐third layers) sequentially and the phylogenetic differences between the first–third layers and the fourth layer were characterized by sequencing the V3–V4 regions of 16S rRNA. A total of 11 phyla, 148 genera, and 308 species were obtained by bioinformatic analysis, and no significant differences between the operational taxonomic unit numbers were observed for these groups. In both groups, the most abundant species were Porphyromonas gingivalis and Fusobacterium nucleatum . Actinomyces naeslundii, Streptococcus intermedius, and Prevotella intermedia possessed relatively high proportions in the first–third layers; while in the fourth layer, both traditional pathogens ( Treponema denticola and Campylobacter rectus ) and novel pathobionts ( Eubacterium saphenum, Filifactor alocis, Treponema sp . HOT238) were prominent. Network analysis showed that either of them exhibited a scale‐free property and was constructed by two negatively correlated components (the pathogen component and the nonpathogen component), while the synergy in the nonpathogen component was lower in the first–third layers than that in the fourth layer. After merging these two parts into a whole plaque group, the negative/positive correlation ratio increased. With potential connections, the first–third layers and the fourth layer showed characteristic key nodes in bacterial networks.